Early Disruption of Cortical Sleep-Related Oscillations in a Mouse Model of Dementia With Lewy Bodies (DLB) Expressing Human Mutant (A30P) Alpha-Synuclein - Stylianou, Myrto; Zaaimi, Boubker; Thomas, Alan; Taylor, John-Paul; LeBeau, Fiona E. N. (Frontiers in Neuroscience, 2020)
Changes in sleep behavior and sleep-related cortical activity have been reported in conditions associated with abnormal alpha-synuclein (-syn) expression, in particular Parkinson’s disease (PD) and dementia with Lewy bodies (DLB). Notably, changes can occur in patients years before the onset of cognitive decline. Sleep-related network oscillations play a key role in memory function, but how abnormal -syn impacts the generation of such activity is currently unclear. To determine whether early changes in sleep-related network activity could also be observed, prior to cognitive dysfunction, we used mice that over-express human mutant -syn (A30P). Recordings in vivo were performed under urethane anaesthesia in the medial prefrontal cortex (mPFC) and CA1 region of the hippocampus in young male (2.5 - 4 months old) A30P and age-matched wild type (WT) mice. We found that the slow oscillation (SO) <1 Hz frequency was significantly faster in both the mPFC and hippocampus in A30P mice, and Up-state-associated fast oscillations at beta (20 - 30 Hz) and gamma (30 - 80 Hz) frequencies were delayed relative to the onset of the Up-state. Spindle (8 - 15 Hz) activity in the mPFC was also altered in A30P mice, as spindles were shorter in duration and had reduced density compared to WT. These changes demonstrate that dysregulation of sleep-related oscillations occurs in young A30P mice long before the onset of cognitive dysfunction. Our data suggest that, as seen in patients, changes in sleep-related oscillations are an early consequence of abnormal -syn aggregation in A30P mice.